EFFECTS OF CREATIVITY-BASED LEARNING (CBL) ON BIOLOGY ACHIEVEMENT AND SCIENTIFIC CREATIVITY OF MATTAYOMSUKSA FOUR STUDENTS - Pinyo , Pimpajee; Chauvatcharin, Nopmamee; Sirisawat, Chade (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to 1) examine the effects of Creativity-Based Learning (CBL) on learning achievement and 2) examine the effects of Creativity-Based Learning (CBL) on scientific creativity in biology among Mattayomsuksa four students. A quasi-experimental design was employed with a cluster random sample of one Mattayomsuksa four classroom from Maryvit School, Chonburi, during the second semester of the 2024 academic year. Research instruments included a CBL-based lesson plan, a biology achievement test, and a scientific creativity assessment. Data were analyzed using descriptive and inferential statistics The results indicated that 1) students’ post-learning biology achievement was significantly higher than their pre-learning scores at the .05 level, 2) students’ post-learning achievement exceeded the 70% benchmark, and 3) students’ scientific creativity scores surpassed the 70% criterion. These findings suggest that CBL effectively enhances both learning achievement and scientific creativity in biology education.